Older men from global settings more vulnerable to clinical changes associated with food insecurity. (30th September 2020) - Pirkle, C; Peltzer, N; Câmara, S; Gomes, J; Ylli, A
Abstract: Background: Studies of the food security status of older adults are rare outside of the United States, especially in low- and middle-income settings. Food insecurity may contribute to disease and disability. Using a diverse sample of older adults, we examine the association of food insecurity with clinical and self-reported measures that are related to disease and impairment. Methods: Cross sectional analysis of 1482 older adults from Kingston and St. Hyacinthe (Canada), Tirana (Albania), Manizales (Colombia), and Natal (Brazil). Outcome measures were Body Mass Index (BMI), waist circumference, and self-reported unintentional weight loss. Food insecurity was assessed with the 9-item Latin American and Caribbean Household Food Security Scale. Covariates were age, sex, study site, and education. Statistical analyses included Student's T-test, Chi-square test, and linear regression. Results: 83% of participants were food secure; 12% experienced mild food insecurity and 5%, moderate/severe food insecurity. Among men, BMI and waist circumference varied significantly by food security status (p < 0.05). Mean BMI among men with moderate/severe food insecurity was 25.5 compared to 27.0 for mild and 27.5 for no food insecurity. The pattern for waist circumference was similar (93.9cm for moderate/severe, 96.7cm for mild, and 98.9cm for no food insecurity). More food insecure men reported unintentional weight loss (13%) than food secure men (10%). This pattern was not observed among women. Statistical adjustment for study site, education, and age did not change the findings. Conclusions: Significant differences in clinical indicators of disease were observed by food security status in men. At the extreme, low BMI and waist circumference are linked to increased risk of malnutrition, compromised immune function, and respiratory and digestive diseases. Differences in these measures by food security status emphasize the need for gender and age specific food security interventions. Key messages: Food insecure men experience clinical indicators of disease significantly more than food insecure women. Successful food security interventions may require sex specific focus across global settings. Little research has been done on food insecurity in elderly outside of North America and study findings contribute to significant gap in sex specific research in this population across global settings.